Gestational weight gain, appetite regulating hormones, and metformin treatment in polycystic ovary syndrome: A longitudinal, placebo‐controlled study. (27th December 2021) - Molin, Johanna; Vanky, Eszter; Løvvik, Tone S.; Dehlin, Eva; Bixo, Marie
Abstract: Objective: To explore mechanisms that modulate gestational weight gain (GWG) in women with polycystic ovary syndrome (PCOS) and healthy controls. Design: Sub‐sample of randomised controlled trials (PCOS) combined with a prospective cohort (controls). Setting: Eleven Norwegian, Swedish, and Icelandic hospitals. Population: Pregnant women with PCOS treated with metformin (PCOS‐M, n  = 36) or placebo (PCOS‐P, n  = 37), and healthy pregnant women (HC, n  = 15). Methods: Serum levels of the appetite regulating hormones leptin, ghrelin, allopregnanolone, and soluble leptin receptor (sOB‐R) were determined in the first and third trimesters. Main Outcome Measures: Excessive GWG (eGWG) relative to body mass index according to Institute of Medicine (IOM) guideline. Serum leptin/sOB‐R ratio, or free‐leptin‐index (FLI), as biomarker of leptin sensitivity. Serum ghrelin and allopregnanolone levels. Results: The overall prevalence of eGWG was 44% (38/86). Women with eGWG had higher first and third trimester FLI ( P  < 0.001), and lower third trimester allopregnanolone levels ( P  = 0.003) versus women with non‐eGWG. The prevalence of eGWG was lower in PCOS‐M versus PCOS‐P (28% versus 62%, odds ratio = 0.4, 95% CI 0.2–0.8, P  = 0.005). FLI decreased during pregnancy in PCOS‐M ( P  = 0.01), but remained unaltered in PCOS‐P and HC. Ghrelin and allopregnanolone levels were comparable in PCOS‐M, PCOS‐P and HC throughout pregnancy. Conclusion: Excessive GWG is associated with enhanced leptin resistance, and attenuated physiological increase in serum allopregnanolone levels during pregnancy. Metformin reduces the risk for eGWG and improves leptin sensitivity in pregnant women with PCOS. Tweetable Abstract: Metformin counteracts excessive weight gain and leptin resistance in pregnant women with polycystic ovary syndrome. Tweetable Abstract: Metformin counteracts excessive weight gain and leptin resistance in pregnant women with polycystic ovary syndrome.